Decrypting the Polyporus dictyopus complex: Recovery of Atroporus Ryvarden and segregation of Neodictyopus gen. nov. (Polyporales, Basidiomyocta) - Palacio, Melissa (2017)
Polyporus dictyopus, with a large number of heterotypic synonyms, has been traditionally considered a species complex, characterized by wide morphological variation and geographic distribution. Thus, neotropical specimens previously identified as P. dictyopus from Amazonia, Cerrado and Atlantic Forest biomes were studied based on detailed macro- and micromorphological examination and phylogenetic analyses, using distinct ribosomal and protein-coding genomic regions: the nuclear ribosomal internal transcribed spacer (nrITS), nuclear ribosomal large subunit (nrLSU), and RNA polymerase II second subunit (RPB2). Two unrelated generic lineages, each one represented by different species, are reported: Atroporus is recovered and re-circumscribed to include A. diabolicus and A. rufoatratus comb. nov.; Neodictyopus gen. nov. is proposed to accommodate N. dictyopus comb. nov. and two new species, N. atlanticae and N. gugliottae. Our study showed that at least five distinct species were hidden under the name P. dictyopus. Detailed descriptions, pictures, illustrations, and a key are provided for Atroporus and Neodictyopus species.